A review of social networking service (SNS) research in communication journals from 2006 to 2011. (August 2015) - Zhang, Yin; Leung, Louis
This article presents a review of the scholarship on social networking services (SNS) in the period from 2006 to 2011. Through a full scan of the academic output published in six high-ranking communication journals listed in the Social Science Citation Index (SSCI) within the six-year period, 84 directly relevant articles were identified. The study summarizes the objects of study, methodological preferences, and thematic patterns of recent SNS research. Challenges to the field and several reflections are addressed. The findings provide not only an overview of current ongoing research trends but also insights for future studies.